Development of Infant Telemonitoring System - Ahmad Taufik, Nur Alyia; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2020)
Infants are commonly well exposed to illness in a challenging environment as they are in the early stage of developing their antibody. Thus, this study is carried out to develop an effective telemonitoring system with accessible data using the ‘Internet of Things (IoT)’. This system is anticipated to help parents monitoring their children throughout the day. Both heart rate and temperature of an infant were measured in real time using the appropriate sensors. Then, sensor circuits sent those data to the microcontroller, Arduino Maker NANO. There are LEDs on the microcontroller to indicate both the infant temperature and heart rate levels. Those data also transferred to the data cloud through the system. ThingSpeak app is used in this system for data storage and could be displayed to end users. An advantage of storing data in cloud is that the users could acquire them in real-time. The system also includes a wearable device in form of a wrist band. Results suggest that the targeted data could be obtained in real time within the preset duration, and simultaneously pushed to the cloud to be stored. The wearable device of this system also strapped comfortably to infants. In conclusion, the developed system could be used to monitor the infant condition since it is capable of providing real time data. In addition, the data stream is secured in cloud storage and could be viewed as in-demand.